2015
DOI: 10.1007/s11837-015-1300-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Powder Reuse Times on Additive Manufacturing of Ti-6Al-4V by Selective Electron Beam Melting

Abstract: An advantage of the powder-bed-based metal additive manufacturing (AM) processes is that the powder can be reused. The powder reuse or recycling times directly affect the affordability of the additively manufactured parts, especially for the AM of titanium parts. This study examines the influence of powder reuse times on the characteristics of Ti-6Al-4V powder, including powder composition, particle size distribution (PSD), apparent density, tap density, flowability, and particle morphology. In addition, tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
171
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(196 citation statements)
references
References 8 publications
17
171
2
6
Order By: Relevance
“…6 Moreover, even at optimal build conditions, in which the former issues are minimized, a large role is played by the actual metal microstructure, which represents the ultimate factor that dictates the mechanical properties of the part.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Moreover, even at optimal build conditions, in which the former issues are minimized, a large role is played by the actual metal microstructure, which represents the ultimate factor that dictates the mechanical properties of the part.…”
Section: Introductionmentioning
confidence: 99%
“…2 In AM, several factors contribute to the ultimate mechanical properties of the part, including the manufacturing technique, 3 the presence of porosity, including incomplete melting, 4 proper thermal control to avoid balling/overmelting, 5 and the quality of the powder feedstock. 6 Moreover, even at optimal build conditions, in which the former issues are minimized, a large role is played by the actual metal microstructure, which represents the ultimate factor that dictates the mechanical properties of the part.…”
Section: Introductionmentioning
confidence: 99%
“…The metal powder must present specific characteristics of: size, shape, granulometric distribution and physical properties (flowability and packing). Powder bed fusion methods can be employed with different granulometric powders sizes [4] [5] [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors describe the performance SLM parts using powders alloys at the range of 20 to 50 μm [4] [5]. The system using electron beam source, as know by electron beam melting (EBM) is widely developing with particles of 76 to 106 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the reuse of Ti6Al4V powder in both selective laser melting (SLM) and selective electron beam melting (SEBM) systems have been published [4,5]. Each of these studies reports the observed changes in the chemical and physical properties of recycled Ti6Al4V powder, and suggests modifications to the manufacturing process to preserve the powder.…”
Section: Introductionmentioning
confidence: 99%